Vision-Based Defects Detection for Glass Production based on Improved Image Processing Method - Rosli, N.S.; Fauadi, M.H.F.M.; Awang, N.F.; Noor, A.Z.M. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Defect is a failure that harms the value, quality or function of a product. In glass manufacturing industry, production defects directly contributes to low quality and a failure for the organization. It will be tiresome process to have manual inspection especially for a large size of glass product. Furthermore, manual inspection processes are typically time consuming and exposed to human error. This article presents a vision-based inspection to detect glass defects using image processing techniques. The result obtained shows that defects can be successfully detected based on the method used.